Method for producing asphalt modifier
The production of an asphalt modifier through polycondensation and controlled cooling enhances compaction and durability of asphalt mixtures, addressing the issue of reduced compaction properties in conventional polyester-containing mixtures.
Patent Information
- Application Number
- JP2020206140
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2020-12-11
- Publication Date
- 2024-12-25
- Estimated Expiration
- 2040-12-11
AI Technical Summary
Asphalt mixtures containing polyester lose compaction properties during on-site kneading, leading to hair cracks and poor appearance due to reduced durability.
A method for producing an asphalt modifier involving polycondensation of an alcohol component and a carboxylic acid component with a catalyst, followed by cooling the polyester into a sheet with a thickness of 1 cm or less, which is then incorporated into an asphalt mixture to enhance compaction and durability.
The method produces an asphalt mixture that is both compactable and durable, improving pavement properties by reducing reaction activity and viscosity during mixing and transportation.
Smart Images

Figure 0007606337000001 
Figure 0007606337000002 
Figure 0007606337000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a method for producing an asphalt modifier, a method for producing an asphalt mixture, and a method for paving roads. [Background technology]
[0002] Asphalt pavement using an asphalt composition is used for paving roads, parking lots, freight yards, sidewalks, etc., because it is relatively easy to lay and the time from the start of paving work to the start of traffic is short. This asphalt pavement has a road surface formed from an asphalt mixture in which aggregate is bound with asphalt, so the paved road has good hardness and durability.
[0003] Patent Document 1 discloses an asphalt composition containing asphalt and a polyester polymer as an asphalt composition suitable for road paving, which can be applied even at low temperatures and maintains stability even at high temperatures. Patent Document 2 discloses a bitumen modifier containing as active ingredients a block copolymer containing specific amounts of a polymer block mainly made of a vinyl aromatic hydrocarbon and a polymer block mainly made of a conjugated diene, and an oil-soluble polyester obtained by condensation polymerization of a polyvalent higher carboxylic acid and a polyhydric alcohol, as a bitumen composition that has excellent solubility in bitumen, excellent toughness, tenacity, and the like, and also has improved low-temperature properties and storage stability. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] Japanese Patent Application Publication No. 04-8766 [Patent Document 2] Japanese Patent Application Publication No. 08-311299 Summary of the Invention [Problem to be solved by the invention]
[0005] While asphalt mixtures containing polyester have traditionally demonstrated excellent durability, they have had problems with losing luster during mixing at the site, adversely affecting compactibility. As a result of the reduced compactibility, hair cracks occur, resulting in a poor appearance of the asphalt pavement. The present invention relates to a method for producing an asphalt modifier that can obtain an asphalt mixture that can form a pavement surface that has both compactibility and durability, a method for producing an asphalt mixture, and a road paving method. [Means for solving the problem]
[0006] The present invention relates to the following [1] to [3]. [1] A method for producing an asphalt modifier containing a polyester, comprising the following steps 1 and 2: Step 1: A step of polycondensing an alcohol component and a carboxylic acid component in the presence of a catalyst to obtain a polyester. Step 2: A step of cooling the polyester obtained in step 1, in which the polyester is in the form of a sheet having a thickness of 1 cm or less upon cooling. [2] A method for producing an asphalt mixture, comprising a step of mixing asphalt, aggregate, and an asphalt modifier obtained by the production method described in [1] above. [3] A road paving method comprising the step of applying the asphalt mixture obtained by the manufacturing method described in [2] above to a road to form an asphalt pavement layer. Effect of the Invention
[0007] According to the present invention, it is possible to provide a method for producing an asphalt modifier, a method for producing an asphalt mixture, and a road paving method, which can obtain an asphalt mixture that forms a pavement surface that combines compactibility and durability. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0008] [Manufacturing method of asphalt modifier] The method for producing an asphalt modifier of the present invention is a method for producing an asphalt modifier containing a polyester, comprising the following steps 1 and 2 in this order. Step 1: A step of polycondensing an alcohol component and a carboxylic acid component in the presence of a catalyst to obtain a polyester. Step 2: A step of cooling the polyester obtained in step 1, in which the polyester is in the form of a sheet having a thickness of 1 cm or less upon cooling.
[0009] The inventors have discovered that by incorporating an asphalt modifier containing a polyester obtained by a manufacturing method including a specific cooling step into an asphalt mixture, a pavement surface that combines compactibility and durability can be formed. The reason why the present invention has an advantageous effect is not clear, but is thought to be as follows. It is believed that the activity of the catalyst derived from the polyester production remains in the polyester, which changes the reactivity of the polyester in the asphalt mixture, causing an increase in the viscosity of the asphalt mixture. The cooling step included in the manufacturing method of the present invention is believed to increase the contact between the polyester and air and the cooling medium when cooling the polyester, which is believed to promote the deactivation of the catalyst in the polyester. This reduces the reactivity of the polyester, and suppresses the increase in viscosity during mixing and transportation of the asphalt mixture. This is believed to improve compaction and pavement properties.
[0010] The definitions of various terms used in this specification are given below. The term "binder mixture" refers to a mixture containing asphalt and a thermoplastic elastomer, and is a concept that includes, for example, asphalt modified with the thermoplastic elastomer described below (hereinafter also referred to as "modified asphalt"). In the polyester, a "structural unit derived from an alcohol component" means a structure obtained by removing a hydrogen atom from a hydroxyl group of an alcohol component, and a "structural unit derived from a carboxylic acid component" means a structure obtained by removing a hydroxyl group from a carboxyl group of a carboxylic acid component. The term "carboxylic acid compound" is a concept that includes not only the carboxylic acid itself, but also anhydrides that decompose during a reaction to generate an acid, and alkyl esters of carboxylic acids (for example, alkyl groups having 1 to 3 carbon atoms). When the carboxylic acid compound is an alkyl ester of a carboxylic acid, the number of carbon atoms of the alkyl group that is the alcohol residue of the ester is not included in the number of carbon atoms of the carboxylic acid compound.
[0011] <Process 1> Step 1 is a step in which an alcohol component and a carboxylic acid component are polycondensed in the presence of a catalyst to obtain a polyester.
[0012] 〔polyester〕 In step 1, a polyester is obtained which is a polycondensation product of an alcohol component and a carboxylic acid component. The polyester contains constitutional units derived from the alcohol component and constitutional units derived from the carboxylic acid component. (Alcohol content) Examples of the alcohol component include aliphatic diols, aromatic diols, and polyhydric alcohols having three or more hydric groups. These alcohol components can be used alone or in combination of two or more kinds.
[0013] From the viewpoint of compaction property and durability, the aliphatic diol is preferably a linear or branched aliphatic diol having from 2 to 12 carbon atoms, and more preferably a linear or branched aliphatic diol having from 2 to 4 carbon atoms. Specific examples of the aliphatic diol include ethylene glycol, 1,2-propanediol, 1,3-propanediol, 1,3-butanediol, 1,4-butanediol, 1,4-butenediol, 1,5-pentanediol, 1,6-hexanediol, neopentyl glycol, 1,10-decanediol, and 1,12-dodecanediol.
[0014] An example of the aromatic diol is an alkylene oxide adduct of bisphenol A. An example of the alkylene oxide adduct of bisphenol A is an alkylene oxide adduct of bisphenol A represented by the formula (I). [ka] [In the formula, OR 1 and R 1 O is an alkylene oxide, and R 1 is an alkylene group having 2 or 3 carbon atoms, x and y are positive numbers indicating the average number of moles of alkylene oxide added, and the sum of x and y is preferably 1 or more, more preferably 1.5 or more, and is preferably 16 or less, more preferably 8 or less, and even more preferably 4 or less.
[0015] Examples of the alkylene oxide adduct of bisphenol A represented by formula (I) include a propylene oxide adduct of bisphenol A [2,2-bis(4-hydroxyphenyl)propane] and an ethylene oxide adduct of bisphenol A. These alkylene oxide adducts of bisphenol A can be used alone or in combination of two or more kinds.
[0016] Examples of trihydric or higher polyhydric alcohols include glycerin, pentaerythritol, trimethylolpropane, and sorbitol.
[0017] From the viewpoints of compactibility and durability, the alcohol component is preferably an aromatic diol. The content of the aromatic diol is preferably 80 mol% or more, more preferably 90 mol% or more, and 100 mol% or less, based on 100 mol% of the alcohol component of the polyester, from the viewpoints of compactibility and durability.
[0018] (Carboxylic acid component) Examples of the carboxylic acid component include an aliphatic dicarboxylic acid compound, an aromatic dicarboxylic acid compound, and a polyvalent carboxylic acid compound having a valence of 3 to 6. These carboxylic acid components can be used alone or in combination of two or more kinds.
[0019] The number of carbon atoms in the main chain of the aliphatic dicarboxylic acid is preferably 3 or more, more preferably 4 or more, and is preferably 10 or less, more preferably 8 or less, from the viewpoints of compactibility and durability. Examples of the aliphatic dicarboxylic acid compound include fumaric acid, maleic acid, oxalic acid, malonic acid, citraconic acid, itaconic acid, glutaconic acid, succinic acid, adipic acid, suberic acid, azelaic acid, sebacic acid, dodecanedioic acid, and succinic acid substituted with an alkyl group having 1 to 20 carbon atoms or an alkenyl group having 2 to 20 carbon atoms. Examples of the substituted succinic acid include dodecylsuccinic acid, dodecenylsuccinic acid, and octenylsuccinic acid. Among the above aliphatic dicarboxylic acid compounds, at least one selected from the group consisting of fumaric acid, maleic acid, and adipic acid is preferred, and adipic acid is more preferred.
[0020] Examples of aromatic dicarboxylic acid compounds include phthalic acid, terephthalic acid, isophthalic acid, naphthalenedicarboxylic acid, anhydrides thereof, and alkyl esters thereof (for example, alkyl groups having carbon atoms of 1 to 3). Among the above aromatic dicarboxylic acid compounds, isophthalic acid and terephthalic acid are preferred, and terephthalic acid is more preferred, from the viewpoints of compaction property and durability.
[0021] The polyvalent carboxylic acid having a valence of 3 to 6 is preferably a trivalent carboxylic acid. Examples of the polyvalent carboxylic acid having a valence of 3 to 6 include trimellitic acid, 2,5,7-naphthalene tricarboxylic acid, pyromellitic acid, and anhydrides thereof. When the polyvalent carboxylic acid is contained, the alcohol component may appropriately contain a monovalent alcohol, and the carboxylic acid component may appropriately contain a monovalent carboxylic acid compound, from the viewpoint of adjusting physical properties.
[0022] As the carboxylic acid component, aromatic dicarboxylic acid is preferred from the viewpoint of compaction property and durability. The content of the aromatic dicarboxylic acid compound is preferably 60 mol% or more, more preferably 70 mol% or more, and preferably 100 mol% or less, more preferably 99 mol% or less, even more preferably 95 mol% or less, and even more preferably 90 mol% or less, based on 100 mol% of the carboxylic acid component, from the viewpoint of improving melt dispersibility in asphalt and compaction property and durability.
[0023] (Structural unit derived from polyethylene terephthalate) The polyester used in the present invention contains structural units consisting of ethylene glycol and terephthalic acid derived from polyethylene terephthalate. The polyethylene terephthalate may contain small amounts of components such as butanediol and isophthalic acid in addition to the structural units consisting of ethylene glycol and terephthalic acid. The polyethylene terephthalate is preferably recycled polyethylene terephthalate.
[0024] In the present invention, the polyester resin may be modified to such an extent that its properties are not substantially impaired. Examples of modified polyester resins include polyester resins grafted or blocked with phenol, urethane, epoxy, or the like by the methods described in JP-A-11-133668, JP-A-10-239903, JP-A-8-20636, etc., and among the modified polyester resins, urethane-modified polyester resins in which polyester resins are urethane-extended with a polyisocyanate compound are preferred.
[0025] (Molar ratio of structural units derived from carboxylic acid components to structural units derived from alcohol components) The molar ratio of the constituent units derived from the carboxylic acid component to the constituent units derived from the alcohol component [carboxylic acid component / alcohol component] is preferably 0.7 or more, more preferably 0.8 or more, even more preferably 0.9 or more, from the viewpoints of adjusting the acid value and of compactibility and durability, and is preferably 1.5 or less, more preferably 1.3 or less, even more preferably 1.1 or less.
[0026] 〔catalyst〕 In step 1, an alcohol component and a carboxylic acid component are polycondensed in the presence of a catalyst to obtain a polyester. Examples of the catalyst include esterification catalysts such as tin catalysts, titanium catalysts, antimony catalysts, and organic acid catalysts. Examples of the tin catalyst include tin(II) compounds that do not have a Sn-C bond, such as di(2-ethylhexanoate)tin(II) and dibutyltin oxide. Examples of the titanium catalyst include titanium diisopropylate bistriethanolaminate. Examples of the antimony catalyst include antimony trioxide. Examples of the organic acid catalyst include sulfonate catalysts such as scandium(III) triflate. As the catalyst, from the viewpoint of reactivity, a tin-based catalyst is preferable, and a tin(II) compound having no Sn-C bond is more preferable.
[0027] From the viewpoints of compactibility and durability, the amount of catalyst used is preferably 0.1 part by mass or more, more preferably 0.15 parts by mass or more, even more preferably 0.2 parts by mass or more, and preferably 2 parts by mass or less, more preferably 1.5 parts by mass or less, even more preferably 1 part by mass or less, and even more preferably 0.7 parts by mass or less, per 100 parts by mass of the alcohol component and the carboxylic acid component combined.
[0028] In the polycondensation reaction, a pyrogallol compound such as gallic acid can be further used as a promoter from the viewpoints of reactivity and cost, and compactibility and durability. The amount of the promoter used is preferably 0.01 or more, more preferably 0.02 or more, even more preferably 0.03 or more, and preferably 0.5 or less, more preferably 0.3 or less, even more preferably 0.2 or less, based on the amount of the esterification catalyst used, in terms of mass ratio. The amount of the promoter used is included in the amount of the catalyst used.
[0029] [Reaction conditions] The temperature of the polycondensation reaction is not particularly limited, but from the viewpoints of reactivity and monomer decomposition temperature, it is preferably 120°C or higher, more preferably 160°C or higher, even more preferably 180°C or higher, and preferably 260°C or lower, more preferably 250°C or lower, even more preferably 240°C or lower. From the viewpoint of reactivity, the reaction time is preferably 1 hour or more, more preferably 2 hours or more, and even more preferably 5 hours or more, and is preferably 20 hours or less, more preferably 15 hours or less, and even more preferably 12 hours or less. The polycondensation reaction of the alcohol component and the carboxylic acid component can be carried out in an inert gas atmosphere from the viewpoint of reactivity.
[0030] In addition to the catalyst, from the viewpoint of compactibility and durability, a polymerization inhibitor such as tertiary butyl catechol may be used in the polycondensation reaction, preferably in an amount of 0.001 part by mass or more, more preferably 0.01 part by mass or more, and preferably 0.5 parts by mass or less, more preferably 0.2 parts by mass or less, and even more preferably 0.1 parts by mass or less, per 100 parts by mass of the total amount of the alcohol component and the carboxylic acid component.
[0031] When the polyester contains constitutional units derived from ethylene glycol derived from polyethylene terephthalate and constitutional units derived from terephthalic acid, the amount of polyethylene terephthalate present in the raw material is preferably 5 to 80 mass%, more preferably 15 to 70 mass%, and even more preferably 25 to 60 mass%, of the total amount of polyethylene terephthalate, the alcohol component, and the carboxylic acid component. By adding polyethylene terephthalate during the polycondensation reaction between the alcohol component and the carboxylic acid component, an ester exchange reaction occurs, and a polyester can be obtained in which the structural units of polyethylene terephthalate are incorporated into structural units derived from the alcohol component and structural units derived from the carboxylic acid component. Polyethylene terephthalate may be present from the start of the polycondensation reaction, or may be added to the reaction system during the polycondensation reaction. From the viewpoint of the rutting resistance and surface aesthetics of the asphalt pavement, the timing of adding polyethylene terephthalate is preferably when the reaction rate between the alcohol component and the carboxylic acid component is 10% or less, more preferably 5% or less. The reaction rate refers to the value of the amount of water produced by reaction (mol) / theoretical amount of water produced (mol)×100.
[0032] The polyester is thus obtained.
[0033] <Process 2> Step 2 is a step of cooling the polyester obtained in step 1, and the polyester at the time of cooling is in the form of a sheet having a thickness of 1 cm or less. 〔cooling〕 In step 2, from the viewpoints of compactibility and durability, the polyester is cooled to preferably 80° C. or less, more preferably 60° C. or less, and even more preferably 40° C. or less. From the viewpoints of compaction and durability, the cooling time in step 2 is preferably 20 minutes or more, more preferably 40 minutes or more, even more preferably 60 minutes or more, and is preferably 8 hours or less, more preferably 6 hours or less, even more preferably 4 hours or less. The cooling means in step 2 may be air cooling, direct water cooling, or indirect water cooling. Also, a steel belt cooler or drum cooler may be used for cooling.
[0034] [Seat] In step 2, the polyester is cooled in the form of a sheet having a thickness of 1 cm or less. The means for forming the polyester into a sheet is not particularly limited, and examples of the method include extrusion molding and cast molding. From the viewpoint of compaction property and durability, the thickness of the sheet when cooled is 1 cm or less, preferably 0.9 cm or less, more preferably 0.7 cm or less, and even more preferably 0.5 cm or less, and preferably 0.1 cm or more, more preferably 0.2 cm or more, and even more preferably 0.3 cm or more. When polyester is made into a sheet by extrusion molding, the thickness can be adjusted by adjusting the extrusion speed. The thickness of the sheet can be measured, for example, by the method described in the Examples.
[0035] The polyester sheet can be used as it is as an asphalt modifier. It can also be further treated by known processes such as pulverization and classification. The pulverization may be coarse pulverization or fine pulverization, or the polyester may be coarsely pulverized and then finely pulverized. Examples of the mill that can be used for coarse pulverization include a hammer mill, an atomizer, a rotoplex, etc. Examples of the mill that can be used for fine pulverization include a fluidized bed jet mill, an impact plate jet mill, a rotary mechanical mill, etc. Thus, an asphalt modifier is produced.
[0036] [Asphalt modifier] The asphalt modifier can be obtained by the above-mentioned production method of the present invention. The asphalt modifier can be mixed with asphalt, for example, to obtain an asphalt composition. The asphalt composition obtained can be used for paving after adding aggregate to prepare an asphalt mixture. The asphalt modifier can be suitably used as a modifier to be blended into an asphalt mixture containing aggregate.
[0037] <Physical properties of polyesters that make up asphalt modifiers> From the viewpoints of compaction ability and durability, the polyester constituting the asphalt modifier preferably exhibits a change in melt viscosity after heating at 180°C for 2 hours of 1-fold or more, more preferably 1.5-fold or more, even more preferably 2.0-fold or more, and preferably 4-fold or less, more preferably 3.8-fold or less, and even more preferably 3.7-fold or less. The change in melt viscosity after heating at 180° C. for 2 hours can be measured by the method described in the Examples below. Specifically, the change in melt viscosity after heating at 180° C. for 2 hours can be calculated by the following formula. Change in melt viscosity after heating at 180°C for 2 hours = (melt viscosity after heating at 180°C for 2 hours [Pa s]) / (melt viscosity before heating at 180°C for 2 hours [Pa s])
[0038] The acid value of the polyester constituting the asphalt modifier is, from the viewpoints of compactibility and durability, preferably 2 mgKOH / g or more, more preferably 5 mgKOH / g or more, even more preferably 10 mgKOH / g or more, and is preferably 40 mgKOH / g or less, more preferably 35 mgKOH / g or less, even more preferably 30 mgKOH / g or less. The hydroxyl value of the polyester constituting the asphalt modifier is, from the viewpoint of compactibility and durability, preferably 1 mgKOH / g or more, more preferably 5 mgKOH / g or more, even more preferably 8 mgKOH / g or more, still more preferably 10 mgKOH / g or more, and is preferably 70 mgKOH / g or less, more preferably 60 mgKOH / g or less, even more preferably 50 mgKOH / g or less, still more preferably 40 mgKOH / g or less. From the same viewpoints as above, the number average molecular weight (Mn) of the polyester constituting the asphalt modifier is preferably 1600 or more, more preferably 2000 or more, even more preferably 2500 or more, and preferably 5000 or less, more preferably 4500 or less, even more preferably 4000 or less. From the same viewpoints as above, the weight average molecular weight (Mw) of the polyester constituting the asphalt modifier is preferably 5,000 or more, more preferably 6,000 or more, even more preferably 7,000 or more, and preferably 30,000 or less, more preferably 20,000 or less, even more preferably 15,000 or less.
[0039] The acid value, hydroxyl value, number average molecular weight (Mn), and weight average molecular weight (Mw) can be measured by the methods described in the Examples. The acid value, hydroxyl value, number average molecular weight (Mn), and weight average molecular weight (Mw) of the polyester constituting the asphalt modifier can be adjusted by the raw material monomer composition, molecular weight, catalyst amount, reaction conditions, or cooling conditions.
[0040] [Asphalt mixture manufacturing method] The asphalt mixture can be obtained by blending asphalt, aggregate, and the asphalt modifier. The method for producing an asphalt mixture of the present invention includes a step of blending asphalt, aggregate, and the asphalt modifier simultaneously or in any order.
[0041] <Asphalt> As the asphalt, various asphalts can be used. For example, in addition to straight asphalt, which is petroleum asphalt for paving, modified asphalt can be mentioned. Modified asphalts include blown asphalt; polymer modified asphalt modified with polymeric materials such as thermoplastic elastomers and thermoplastic resins, and the like. Straight asphalt is a residual bituminous material obtained by subjecting crude oil to atmospheric distillation equipment, vacuum distillation equipment, and the like. Blown asphalt means asphalt obtained by heating a mixture of straight asphalt and heavy oil, and then blowing air into it to oxidize it. The asphalt is preferably selected from the group consisting of straight asphalt and polymer modified asphalt, and modified asphalt is more preferable from the viewpoint of compaction and durability of asphalt pavement, and straight asphalt is more preferable from the viewpoint of versatility.
[0042] (Thermoplastic elastomer) Examples of the thermoplastic elastomer in the polymer modified asphalt include styrene / butadiene block copolymer (hereinafter also referred to as "SB"), styrene / butadiene / styrene block copolymer (hereinafter also referred to as "SBS"), styrene / butadiene random copolymer (hereinafter also referred to as "SBR"), styrene / isoprene block copolymer (hereinafter also referred to as "SI"), styrene / isoprene / styrene block copolymer (hereinafter also referred to as "SIS"), styrene / isoprene random copolymer (hereinafter also referred to as "SIR"), ethylene / vinyl acetate copolymer, ethylene / acrylic acid ester copolymer, styrene / ethylene / butylene / styrene copolymer, styrene / ethylene / propylene / styrene copolymer, polyurethane-based thermoplastic elastomer, polyolefin-based thermoplastic elastomer, isobutylene / isoprene copolymer, polyisoprene, polychloroprene, synthetic rubber other than the above, and at least one selected from natural rubber. Among these, from the viewpoint of compaction property and durability of asphalt pavement, the thermoplastic elastomer is preferably at least one selected from SB, SBS, SBR, SI, SIS, SIR, and ethylene / acrylic acid ester copolymer, more preferably at least one selected from SB, SBS, SBR, SI, SIS, and SIR, and even more preferably at least one selected from SBR and SBS. From the viewpoint of compaction properties and durability of asphalt pavement, the amount of thermoplastic elastomer in the polymer modified asphalt is, based on 100% by mass of the asphalt composition, preferably 0.1% by mass or more, more preferably 0.5% by mass or more, even more preferably 1% by mass or more, still more preferably 2% by mass or more, and preferably 30% by mass or less, more preferably 20% by mass or less, even more preferably 10% by mass or less, and still more preferably 5% by mass or less.
[0043] <Aggregate> The aggregate may be any material selected from crushed stone, boulders, gravel, sand, recycled aggregate, ceramics, etc. In addition, the aggregate may be either coarse aggregate with a particle size of 2.36 mm or more, or fine aggregate with a particle size of less than 2.36 mm. Examples of coarse aggregate include crushed stone with a particle size range of 2.36 mm or more and less than 4.75 mm, crushed stone with a particle size range of 4.75 mm or more and less than 12.5 mm, crushed stone with a particle size range of 12.5 mm or more and less than 19 mm, and crushed stone with a particle size range of 19 mm or more and less than 31.5 mm. The fine aggregate is preferably one having a particle size of 0.075 mm or more and less than 2.36 mm. Examples of fine aggregate include river sand, dune sand, mountain sand, sea sand, crushed sand, fine sand, screenings, crushed stone dust, silica sand, artificial sand, glass cullet, foundry sand, and recycled crushed aggregate sand. The above particle size is the value specified in JIS A5001:2008. Among these, a combination of coarse aggregate and fine aggregate is preferable.
[0044] The fine aggregate may contain a filler having a particle size of less than 0.075 mm. Examples of the filler include sand, fly ash, calcium carbonate such as limestone powder, slaked lime, etc. Among these, calcium carbonate is preferred from the viewpoint of improving the strength of the asphalt pavement. From the viewpoint of improving pavement strength, the average particle size of the filler is preferably 0.001 mm or more, and preferably 0.06 mm or less, more preferably 0.04 mm or less, and further preferably 0.03 mm or less. The average particle size of the filler can be measured by a laser diffraction particle size distribution measuring device. Here, the average particle size means the average particle size at 50% cumulative volume.
[0045] From the viewpoints of compactibility and durability, the mass ratio (content or mixing amount) of coarse aggregate to fine aggregate is preferably 10 / 90 or more, more preferably 20 / 80 or more, even more preferably 30 / 70 or more, and is preferably 90 / 10 or less, more preferably 80 / 20 or less, even more preferably 70 / 30 or less.
[0046] Suitable examples of blending the asphalt mixture include the following (1) to (3). (1) Fine-grade asphalt containing 30% to less than 45% by volume of coarse aggregate, 30% to 50% by volume of fine aggregate, and a total of 5% to 10% by volume of asphalt and asphalt modifiers. (2) Dense-graded asphalt containing 45% to less than 70% by volume of coarse aggregate, 20% to 45% by volume of fine aggregate, and a total of 3% to 10% by volume of asphalt and asphalt modifiers. (3) Porous asphalt containing 70% by volume or more and 80% by volume or less of coarse aggregate, 10% by volume or more and 20% by volume or less of fine aggregate, and a total of 3% by volume or more and 10% by volume or less of asphalt and asphalt modifier.
[0047] From the viewpoint of compactibility and durability, the content of aggregate is preferably 1,000 parts by mass or more, more preferably 1,200 parts by mass or more, and even more preferably 1,400 parts by mass or more, per 100 parts by mass of the total of asphalt and asphalt modifier, and is preferably 3,000 parts by mass or less, more preferably 2,500 parts by mass or less, and even more preferably 2,000 parts by mass or less.
[0048] The proportion of asphalt in conventional asphalt mixtures containing aggregate and asphalt is usually determined based on the optimal amount of asphalt obtained from the "Mix Design of Asphalt Composition" described in the "Guidelines for Pavement Design and Construction" issued by the Japan Road Association, a public interest incorporated association. In the present invention, the above-mentioned optimum amount of asphalt corresponds to the total amount of asphalt and the asphalt modifier consisting of polyester. However, it is not necessary to be limited to the method described in the "Guidelines for Pavement Design and Construction" and it may be determined by other methods.
[0049] <Asphalt modifier content> The content of the asphalt modifier in the asphalt mixture is preferably 1 part by mass or more, more preferably 5 parts by mass or more, and even more preferably 8 parts by mass or more, per 100 parts by mass of asphalt from the viewpoint of compaction ability and durability of the asphalt pavement, and from the viewpoint of workability, it is preferably 40 parts by mass or less, more preferably 35 parts by mass or less, and even more preferably 30 parts by mass or less.
[0050] The asphalt mixture may further contain other components as necessary.
[0051] <Asphalt mixture manufacturing method> Specific methods for producing asphalt mixtures include conventional methods for producing asphalt mixtures called the plant mix method and the premix method. All of these methods involve adding asphalt and polyester to heated aggregate. Examples of the addition method include the premix method in which asphalt and the asphalt modifier are dissolved in advance, and the plant mix method in which the asphalt modifier is added to asphalt. More specifically, in the method for producing an asphalt mixture, in the mixing step, preferably, (i) adding and mixing asphalt to the heated aggregate, and then adding and mixing the asphalt modifier; (ii) Simultaneously adding and mixing the asphalt and asphalt modifier to the heated aggregate; or (iii) A pre-mixed mixture of asphalt and asphalt modifier is added to and mixed with the heated aggregate.
[0052] The temperature of the heated aggregate in methods (i) to (iii) is preferably 130°C or higher, more preferably 160°C or higher, and even more preferably 180°C or higher, from the viewpoint of compaction and durability of the asphalt pavement, and is preferably 230°C or lower, more preferably 210°C or lower, and even more preferably 200°C or lower, from the viewpoint of preventing thermal deterioration of the asphalt.
[0053] In the mixing step, from the viewpoint of compaction and durability of the asphalt pavement, the mixing temperature is preferably 130° C. or higher, more preferably 150° C. or higher, even more preferably 170° C. or higher, and even more preferably 180° C. or higher, and from the viewpoint of preventing thermal deterioration of the asphalt, it is preferably 230° C. or lower, more preferably 210° C. or lower, and even more preferably 200° C. or lower. The mixing time in the mixing step is not particularly limited, and is preferably 30 seconds or more, more preferably 1 minute or more, even more preferably 2 minutes or more, and even more preferably 5 minutes or more, and the upper limit of the time is not particularly limited, and is preferably about 30 minutes.
[0054] From the viewpoint of compaction and durability of the asphalt pavement, the method for producing an asphalt mixture preferably includes a step of holding the resulting mixture at the above-mentioned mixing temperature after the mixing step. In the holding step, the mixture may be further mixed, but it is sufficient that the mixture is held at the aforementioned temperature or higher. In the holding step, the mixing temperature is preferably 130° C. or higher, more preferably 150° C. or higher, even more preferably 170° C. or higher, and even more preferably 180° C. or higher, and from the viewpoint of preventing thermal deterioration of the asphalt mixture, is preferably 230° C. or lower, more preferably 210° C. or lower, and even more preferably 200° C. or lower. The holding time in the holding step is preferably 0.2 hours or higher, more preferably 0.3 hours or higher, and even more preferably 0.5 hours or higher, and the upper limit of the time is not particularly limited, but is, for example, about 5 hours.
[0055] [Road paving method] The asphalt mixture is suitable for road paving and is used for road paving. The road paving method of the present invention includes a step of applying the above-mentioned asphalt mixture to a road to form an asphalt pavement layer. Specifically, the road paving method includes a step (step 1) of mixing asphalt, the above-mentioned crystalline polyester, and aggregate to obtain an asphalt mixture, and a step (step 2) of applying the asphalt mixture obtained in step 1 to a road to form an asphalt pavement layer. The asphalt pavement layer is usually a base layer or a surface layer, and is preferably a surface layer from the viewpoints of compaction property and durability.
[0056] From the viewpoint of compaction and durability, the thickness of the asphalt pavement material layer is preferably 3 cm or more, more preferably 4 cm or more, and even more preferably 4.5 cm or more, and is preferably 7 cm or less, more preferably 6 cm or less, and even more preferably 5.5 cm or less. The asphalt mixture may be compacted and applied in a similar manner using a known construction machine. The compaction temperature when used as a heated asphalt mixture is preferably 100°C or higher, more preferably 120°C or higher, and even more preferably 130°C or higher, from the viewpoints of compactibility and durability, and is preferably 200°C or lower, more preferably 180°C or lower.
[0057] The asphalt mixture may be compacted and applied in a similar manner using a known construction machine. The compaction temperature when used as a heated asphalt mixture is preferably 100°C or higher, more preferably 120°C or higher, and even more preferably 130°C or higher, from the viewpoints of compactibility and durability, and is preferably 200°C or lower, more preferably 180°C or lower. EXAMPLES
[0058] Various physical properties were measured and evaluated by the following methods. In the following examples and comparative examples, parts and percentages are by weight unless otherwise specified.
[0059] (1) Acid value and hydroxyl value of polyester The acid value and hydroxyl value of the polyester were measured according to the method of JIS K0070: 1992. However, the measurement solvent was changed from the mixed solvent of ethanol and ether specified in JIS K0070: 1992 to a mixed solvent of acetone and toluene (acetone:toluene = 1:1 (volume ratio)).
[0060] (2) Number average molecular weight (Mn) and weight average molecular weight (Mw) of polyester The number average molecular weight and the weight average molecular weight were determined by gel permeation chromatography (GPC) according to the following method. (i) Preparation of sample solution The sample was dissolved in chloroform at 40° C. to a concentration of 0.5 g / 100 mL. Next, this solution was filtered using a PTFE-type membrane filter “DISMIC-25JP” (manufactured by Toyo Roshi Kaisha, Ltd.) with a pore size of 0.20 μm to remove insoluble components, and a sample solution was obtained. (ii) Molecular weight measurement The following measuring device and analytical column were used, and chloroform was used as the eluent at a flow rate of 1 mL per minute. The column was stabilized in a thermostatic chamber at 40°C. 200 μL of the sample solution was injected into the column and the measurement was performed. The molecular weight of the sample was calculated based on a calibration curve that had been prepared in advance. The calibration curve used here included several types of monodisperse polystyrene (A-500 (5.0 × 10 2 ), A-1000(1.01×10 3 ), A-2500(2.63×10 3 ), A-5000(5.97×10 3 ), F-1(1.02×10 4 ), F-2(1.81×10 4 ), F-4(3.97×10 4 ), F-10(9.64×10 4 ), F-20(1.90×10 5 ), F-40(4.27×10 5 ), F-80(7.06×10 5 ), F-128(1.09×10 6 )) was used as a standard sample. The numbers in parentheses indicate the molecular weight. Measuring device: "HLC-8320GPC" (Tosoh Corporation) Analytical column: "TSKgel Super HZM" + "TSKgel Super H-RC" x 2 (manufactured by Tosoh Corporation)
[0061] (3) Measurement of polyester melt viscosity The melt viscosity of the polyester was measured at a test temperature of 180° C. in accordance with the Japan Petroleum Institute Standard JPI-5s-54-99: Asphalt - Viscosity test method using a rotational viscometer. Specifically, 50 g of polyester was weighed into a measurement cell and heated in an oven for 30 minutes to obtain a molten sample, which was then stirred at 180°C for 2 hours. The measurements were performed using a Brookfield viscometer ("DV1 VISCOMETER"; spindle: SC4-27, chamber: SC4-13R) at 20 rpm (upper limit 12,500 mPa s). However, for samples exceeding the upper limit, measurements were performed at 5 rpm (upper limit 50,000 mPa s). (4) Thickness measurement of polyester sheet A metal needle was inserted into five places on the polyester sheet, and the length of the polyester attached to the metal needle was measured. The average of the measured lengths was taken as the thickness of the polyester sheet.
[0062] Production Example 1 (Asphalt Modifier AM1) The polyester alcohol components shown in Table 1 and terephthalic acid were placed in a 5-liter four-neck flask equipped with a thermometer, a stainless steel stirring rod, a downflow condenser, and a nitrogen inlet tube, and tin(II) di(2-ethylhexanoate) and gallic acid were added in a nitrogen atmosphere. The mixture was heated to 235°C over 3 hours in a mantle heater and maintained at 235°C for 7 hours. The reaction was carried out under reduced pressure of 8.0 kPa until the softening point shown in Table 1 was reached. 9000 g of the obtained polyester A1 was poured into a 150 mm square mold made of aluminum foil. The thickness of the polyester sheet at this time was 4 mm. The polyester sheet was solidified while being cooled at room temperature for 2 hours. The solidified polyester sheet was then taken out and crushed to obtain asphalt modifier AM1. The results are shown in Table 1.
[0063] Production Example 2 (Asphalt Modifier AM2) The raw materials other than adipic acid shown in Table 1 were placed in a 5-liter four-neck flask equipped with a thermometer, a stainless steel stirring rod, a downflow condenser, and a nitrogen inlet tube, and tin (II) di(2-ethylhexanoate) and gallic acid were added in a nitrogen atmosphere. The temperature was raised to 235°C in a mantle heater, and after reaching 235°C, the mixture was held for 7 hours, and then the reaction was carried out under reduced pressure at 8.0 kPa for 1 hour. After that, the mixture was cooled to 180°C, and adipic acid was added. The mixture was heated to 210°C over 2 hours, and then held at 210°C for 1 hour, and the reaction was carried out under reduced pressure until the softening point shown in Table 1 was reached. 9000 g of the obtained polyester B1 was poured into a 150 mm square mold made of aluminum foil. The thickness of the polyester sheet at this time was 4 mm. The polyester sheet was cooled at room temperature for 2 hours to solidify. The solidified polyester sheet was then taken out and coarsely pulverized to obtain asphalt modifier AM2. The results are shown in Table 1.
[0064] Production Example 3 (Asphalt Modifier AM3) The raw material monomers shown in Table 1 were placed in a 5 L four-neck flask equipped with a nitrogen inlet tube, a dehydration tube, a stirrer, and a thermocouple, and tin(II) di(2-ethylhexanoate) was added under a nitrogen atmosphere. The mixture was maintained at 140°C for 6 hours and then heated to 210°C over a period of 6 hours. The mixture was then reacted at 210°C for 1 hour and then at 8.3 kPa for 1 hour. 9000 g of the obtained polyester C1 was poured into a 150 mm square mold made of aluminum foil. The thickness of the polyester sheet at this time was 4 mm. The polyester sheet was solidified while being cooled at room temperature for 2 hours. The solidified polyester sheet was then taken out and coarsely pulverized to obtain asphalt modifier AM3. The results are shown in Table 1.
[0065] Production Examples 4 and 5 (Asphalt Modifiers AM4 and AM5) Polyesters A2 and A3 were obtained in the same manner as in Production Example 1, except that the raw material monomers shown in Table 1 were used. 9000 g of the obtained polyester was poured into a 150 mm square mold made of aluminum foil. The polyester sheet had a thickness of 4 mm. The polyester sheet was cooled at room temperature for 2 hours to solidify. The solidified polyester sheet was then taken out and coarsely pulverized to obtain asphalt modifiers AM4 and AM5. The results are shown in Table 1.
[0066] Production Examples 6 to 8 (Asphalt Modifiers AM6 to AM8) Polyesters A4 to A6 were obtained in the same manner as in Production Example 1, except that the raw material monomers shown in Table 2 were used. 9000 g of the resulting polyester was poured into a 150 mm square mold made of aluminum foil. The polyester sheet had a thickness of 4 mm. An excess of water was then poured onto the polyester. The polyester sheet was allowed to solidify while cooling at room temperature for 2 hours. The solidified polyester sheet was then taken out and coarsely pulverized to obtain asphalt modifiers AM6 to AM8. The results are shown in Table 2.
[0067] Production Example 9 (Asphalt Modifier am1) Polyester a1 was obtained in the same manner as in Production Example 7. 9000 g of the resulting polyester was poured into a steel tray (No. 12; 43 x 30 cm). The polyester sheet had a thickness of 65 mm. An excess of water was then poured onto the polyester. The polyester sheet was allowed to solidify while cooling at room temperature for 2 hours. The solidified polyester sheet was then taken out and coarsely crushed to obtain asphalt modifier am1. The results are shown in Table 2.
[0068] Production Example 10 (Asphalt Modifier am2) In the same manner as in Production Example 8, polyester a2 was obtained. 9000 g of the resulting polyester was poured into a steel tray (No. 12; 43 x 30 cm). The polyester sheet had a thickness of 65 mm. An excess of water was then poured onto the polyester. The polyester sheet was allowed to solidify while cooling at room temperature for 2 hours. The solidified polyester sheet was then taken out and coarsely crushed to obtain asphalt modifier am2. The results are shown in Table 2.
[0069] [Table 1]
[0070] [Table 2]
[0071] The abbreviations for the alcohol components used are as follows: BPA-EO: Polyoxyethylene (2.2 moles) adduct of bisphenol A BPA-PO: Polyoxypropylene (2.2 moles) adduct of bisphenol A
[0072] Example 1 15 kg of aggregate heated to 180°C (see below for the composition of aggregate) was placed in an asphalt mixer and mixed at 180°C for 60 seconds. Next, 822 g of modified type II asphalt (manufactured by Toa Road Industry Co., Ltd., "HR Binder") was added and mixed for 1 minute in the asphalt mixer. Furthermore, 164 g of the asphalt modifier AM1 obtained in Production Example 1 was added and mixed for 2 minutes to obtain an asphalt mixture. The resulting asphalt mixture was stored at 180°C for 15 minutes, after which approximately 1,200 g of the mixture was filled into a formwork and compacted on both sides 50 times using an automatic asphalt compaction device (NA-507) manufactured by Nakajima Gihan Co., Ltd. After that, it was left to cool to room temperature over 15 hours, and cylindrical asphalt specimen M-1 with a diameter of 100 mm and a thickness of approximately 63 mm was obtained.
[0073] <Aggregate composition> No. 6 crushed stone 50.9 parts by weight Crushed sand 1 10.4 parts by mass Crushed sand 2 22.1 parts by mass Fine sand 10.4 parts by mass Stone powder (calcium carbonate) 6.2 parts by weight Passed mass%: Sieve size 15 mm: 100% by mass Sieve size 10 mm: 85.6% by mass Sieve size 5 mm: 49.7% by mass Sieve size 2.5 mm: 44.6% by mass Sieve size 1.2 mm: 31.6% by mass Sieve size 0.6 mm: 21.3% by mass Sieve size 0.3 mm: 12.7% by mass Sieve size 0.15mm: 7.1% by mass
[0074] Examples 2 to 9, Comparative Examples 1 to 3 Except for changing the blend ratio as shown in Table 3, asphalt specimens M-2 to M-9 and M-a1 to M-a3 were prepared in the same manner as in Example 1.
[0075] [evaluation] [Marshall stability] Using a Marshall testing machine (manufactured by Nakajima Gihan Co., Ltd., "Model No.-504"), the sides of an asphalt specimen were sandwiched between two arc-shaped loading plates, and a load was applied in the diameter direction at a loading rate of 50 mm / min with the specimen temperature at 70°C until it broke. The maximum load until it broke was taken as the Marshall stability. The higher the Marshall stability value, the more durable the asphalt pavement. The results are shown in Table 3.
[0076] [Filling degree] (Filling degree) The filling degree of the asphalt specimen was calculated according to the following formula. Filling degree = (void ratio when polyester is not added) / (void ratio when polyester is added) (porosity) The void ratio used to calculate the packing degree was calculated according to the following formula. Porosity = 100 x {1-(specimen bulk density) / (theoretical density)} (Each physical property value) Each physical property used to calculate the porosity was calculated according to the following formula. Bulk density of specimen = (mass in air) / (surface dry mass - mass in water) Theoretical density = 1 / [{(1-asphalt addition rate) / 100) / aggregate specific gravity (surface dry)}+(asphalt addition rate) / 100 / 1.04] The surface dry weight is the mass of the test specimen after it has been immersed in water for 3 minutes and then the surface has been wiped. The aggregate specific gravity (surface dry) is the specific gravity taking into account asphalt absorption, and was set to a constant of 2.618. The results are shown in Table 3.
[0077] [Table 3]
[0078] It is clear that the asphalt modifier made of polyester obtained by the production method of the present invention makes it possible to obtain an asphalt mixture that forms a pavement surface that is both compactable and durable.
Claims
1. A method for producing an asphalt modifier containing a polyester, comprising the following steps 1 and 2: Step 1: A step of polycondensing an alcohol component and a carboxylic acid component in the presence of a catalyst to obtain a polyester. Step 2: A step of cooling the polyester obtained in step 1 to 80° C. or less, the cooling time being 20 minutes or more, and the polyester being in the form of a sheet having a thickness of 1 cm or less upon cooling.
2. The method for producing an asphalt modifier according to claim 1, wherein the catalyst in step 1 comprises one or more selected from a tin-based catalyst, a titanium-based catalyst, an antimony-based catalyst, and an organic acid catalyst.
3. The method for producing an asphalt modifier according to claim 1 or 2, wherein the amount of the catalyst used in step 1 is 0.1 parts by mass or more and 2 parts by mass or less per 100 parts by mass of the alcohol component and the carboxylic acid component combined.
4. The method for producing an asphalt modifier according to any one of claims 1 to 3, wherein the change in melt viscosity of the polyester after heating at 180°C for 2 hours is 1 to 4 times.
5. A method for producing an asphalt mixture, comprising a step of mixing asphalt, aggregate, and an asphalt modifier obtained by the production method according to any one of claims 1 to 4.
6. The method for producing an asphalt mixture according to claim 5, wherein the asphalt is straight asphalt or modified asphalt.
7. The method for producing an asphalt mixture according to claim 6, wherein the modified asphalt is an asphalt modified with a thermoplastic elastomer.
8. The method for producing an asphalt mixture according to claim 7, wherein the thermoplastic elastomer is at least one selected from the group consisting of styrene / butadiene block copolymers, styrene / butadiene / styrene block copolymers, styrene / butadiene random copolymers, styrene / isoprene block copolymers, styrene / isoprene / styrene block copolymers, styrene / isoprene random copolymers, ethylene / vinyl acetate copolymers, and ethylene / acrylic acid ester copolymers.
9. A road paving method comprising a step of applying an asphalt mixture obtained by the manufacturing method according to any one of claims 5 to 8 to a road to form an asphalt pavement layer.
Citation Information
Patent Citations
JP1973008307U
Asphalt composition
JP1992008766A
Bitumen modifier and bitumen composition
JP1996311299A
Asphalt composition for road paving
JP2019508608A
Interpenetrating elastomeric networks derived from ground tire rubber particles
JP2021509694A
